Rand McNally & Co.'s new official railroad map of the United States : With portions of the dominion of Canada, the Republic of Mexico, and the West Indies. - Rand McNally and Company (Rand McNally and Company, 1898)
Map shows state boundaries for the United States, Mexico, the West Indies, and lower portion of Canada; major cities and towns, military posts, Native American reservations, and railroads; Oklahoma and "Indian Territory." Inset: "Map of Alaska." Relief shown by hachures and spot heights. Scale [ca. 1:5,195,520].